2006
DOI: 10.1089/jir.2006.26.827
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Differences Between Macrophages and Dendritic Cells in the Cyclic AMP-Dependent Regulation of Lipopolysaccharide-Induced Cytokine and Chemokine Synthesis

Abstract: Cyclic adenosine monophosphate (cAMP) is an intracellular signaling molecule responsible for directing cellular responses to extracellular signals. Once believed to signal exclusively through its ability to bind protein kinase A (PKA), recent research has revealed alternative cAMP-binding targets involved in PKA-independent processes. In this study we addressed the hypothesis that the guanine nucleotide exchange protein directly activated by cAMP (Epac-1) and PKA differentially regulate inflammatory mediator p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 28 publications
7
68
0
1
Order By: Relevance
“…First, IL-6 is well recognized to be regulated by cAMP and, in particular, both PGE 2 and PGI 2 have been shown to modulate its synthesis during LPS stimulation (34,35). Second, in the rat model both AM and PM IL-6 synthesis are profoundly regulated by PGE 2 under conditions of LPS treatment (13). Lastly, as discussed below, IL-6 production by human AMs has been shown to be regulated by treprostinil during LPS exposure (29).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…First, IL-6 is well recognized to be regulated by cAMP and, in particular, both PGE 2 and PGI 2 have been shown to modulate its synthesis during LPS stimulation (34,35). Second, in the rat model both AM and PM IL-6 synthesis are profoundly regulated by PGE 2 under conditions of LPS treatment (13). Lastly, as discussed below, IL-6 production by human AMs has been shown to be regulated by treprostinil during LPS exposure (29).…”
Section: Discussionmentioning
confidence: 98%
“…Our treatments were brief (minutes) in the studies of cAMP elevation, FcR-mediated phagocytosis, and bacterial killing, whereas PPAR␤ is a transcription factor whose effects would be expected to require a number of hours. Though it remains possible that the effect of treprostinil on cytokine synthesis involved the PPAR␤ system because those experiments were conducted in the presence of treprostinil for Ͼ16 h, we have previously shown that cAMP signaling mechanisms are sufficient to explain such results (13). The finding that treprostinil is more promiscuous in binding G protein-coupled receptors than previously thought warns us against assuming that the pharmacological effects of this drug in vivo result from IP-mediated signaling exclusively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such metabolites, known as eicosanoids, are generated in abundance at sites of inflammation (e.g. the host-microbial interface) and influence key components of the innate immune system, namely, phagocytosis [2,3], intracellular microbial killing [4,5], and inflammatory mediator generation [6].…”
Section: Introductionmentioning
confidence: 99%